The japanese mind eaudiobook Understanding contemporary japanese culture. - Davies, Roger J. (Tantor Media, 2019)
In The Japanese Mind , Roger Davies offers Westerners an invaluable key to the unique aspects of Japanese culture. Listeners of this book will gain a clear understanding of what makes the Japanese, and their society, tick. Among the topics explored: aimai (ambiguity), amae (dependence upon others' benevolence), amakudari (the nation's descent from heaven), chinmoku (silence in communication), gambari (perseverance), giri (social obligation), haragei (literally, "belly art"; implicit, unspoken communication), kenkyo (the appearance of modesty), sempai-kohai (seniority), wabi-sabi (simplicity and elegance), and zoto (gift giving), as well as discussions of child-rearing, personal space, and the roles of women in Japanese society. All in all, this book is an easy-to-use introduction to the distinguishing characteristics of Japanese society; an invaluable resource for anyone—business people, travelers, or students—perfect for course adoption, but also for anyone interested in Japanese culture.